2018
DOI: 10.1002/jcp.26554
|View full text |Cite
|
Sign up to set email alerts
|

ROS‐Autophagy pathway mediates monocytes‐human umbilical vein endothelial cells adhesion induced by apelin‐13

Abstract: Apelin is the endogenous ligand of APJ receptor. Both monocytes (MCs) and human umbilical vein endothelial cells (HUVECs) express apelin and APJ, which play important roles in the physiological processes of atherosclerosis. Our previous research indicated that apelin-13 promoted MCs-HUVECs adhesion. Here, we further explore the mechanism responsible for MCs-HUVECs adhesion induced by apelin-13. Apelin-13 promoted reactive oxygen species (ROS) generation and NOX4 expression in HUVECs. Apelin-13 inducedautophagy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 53 publications
2
18
0
Order By: Relevance
“…The molecular mechanism underlying autophagy has been extensively investigated in recent years. The mitochondrial antioxidant Mito-TEMPO (mitochondrial-targeted SOD mimetic) enhanced SOD2 activity but not SOD2 levels, significantly suppressed the 5-ALA-PDT-mediated increase in autophagy level, and consistent with many studies revealed that ROS can induce autophagy [34] , [35] , [36] .…”
Section: Discussionsupporting
confidence: 83%
“…The molecular mechanism underlying autophagy has been extensively investigated in recent years. The mitochondrial antioxidant Mito-TEMPO (mitochondrial-targeted SOD mimetic) enhanced SOD2 activity but not SOD2 levels, significantly suppressed the 5-ALA-PDT-mediated increase in autophagy level, and consistent with many studies revealed that ROS can induce autophagy [34] , [35] , [36] .…”
Section: Discussionsupporting
confidence: 83%
“…For example, a previous study demonstrates that apelin reduces oxidative stress and prevents pressure-overloadinduced left ventricular hypertrophy 44 . By contrast, there is increasing evidence proving that apelin-13 induces cardiac hypertrophy by increasing the production of ROS and the expression levels of NADPH oxidases in vivo and in vitro [45][46][47] . In addition, apelin/APJ in paraventricular nucleus is found to induce long-term high BP and renal sympathetic nerve activity via increasing oxidative stress 37,48 .…”
Section: Discussionmentioning
confidence: 98%
“…In addition, it is known that the regulatory effects of apelin on oxidative stress are conducted by binding to its receptor APJ in most experimental conditions 37,46,47 . As another endogenous ligand, it is still unclear whether ELA is dependent on APJ to suppress DOCA/salt-induced NADPH oxidase/ROS/NLRP3 signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…(f) Representative western blots analysis of Drp1, Mfn1, Mfn2, and OPA1 expressions in human aortic VSMC infected with siRNA AMPKα or siRNA scramble transfection (n = 3 *p < 0.05 and **p < 0.01 vs. control, # p < 0.01, ## p < 0.01 vs. apelin-13). CCK-8: cell counting kit-8; FBS: fetal bovine serum; PBS: phosphatebuffered saline; VMSC: vascular smooth muscle cell M. Liu et al, 2018). Moreover, it has been widely reported that apelin and APJ are upregulated in heart of hypertensive rats and human autopsy atherosclerotic coronary artery (Pitkin, Maguire, Kuc, & Davenport, 2010;Sekerci, Acar, Tepekoy, Ustunel, & Keles-Celik, 2018).…”
Section: Discussionmentioning
confidence: 99%